A kinetic modeling of particle formation by gas antisolvent process: Precipitation of aspirin. Issue 5 (4th May 2017) - Jafari, D.; Nowee, S. M.; Noie, S. H.
ABSTRACT: Population balance equations (PBEs) are often integro-partial differential in nature due to complexities involved in nonconventional crystallization processes, especially gas antisolvent (GAS). The reason is that they include phenomena such as primary nucleation, secondary nucleation, crystal growth, agglomeration, and/or breakage of crystals. Therefore, the solution to such models has become rather difficult. Considering these difficulties, a powerful numerical algorithm was adopted in this paper to treat the population balance model for the precipitation of aspirin by the GAS process. This method was the combination of Lax–Wendroff and Crank–Nicholson numerical methods. It was used to investigate the effect of significant operating parameters, that is, antisolvent addition rate, process temperature, and solute concentration, on the final product properties for two solvents. The antisolvent addition rate was varied between 8 and 40 bar/min, the process temperature was kept constant at levels 37°C and 42°C, the solute concentration was manipulated at two levels, namely, 0.2 and 0.27 g solute/g solution, and methanol and acetone were used as the organic solvents. The results indicated the successful performance of the applied method in treating PBE, since smooth particle size distributions were produced, which were in an acceptable agreement with the experimental data of the investigated system. GRAPHICAL ABSTRACT: